Descripción de los principales aspectos clinicopatologicos de la hematuria enzoótica bovina (2021)
Bovine Enzootic Hematuria is recognized as an endemic disease defined as a chronic toxicosis that has become relevant in the recent world environment, it is characterized by producing anemia and death in animals that are between 4 and 12 years of age, mainly presenting lesions in the neoplastic and non-neoplastic urinary bladder, generally caused by ingestion of male fern. Considering the large number of cattle found in the country established in the length and breadth of the width of the country, the present monograph had the intention of characterizing the main clinical-pathological aspects of the disease, considering as study methodology the documentary review. Under this purpose, different studies were identified that coincide in recognizing that a fundamental step in the diagnosis of the disease is the observation, both of blood in the urine, as well as the meat-bone composition of the animals, because the pathology tends to generate a constant degradation of the healthy conditions of the bovine generating death due to anemia or malnutrition. To the same extent, it is recognized that both clinical and mechanical procedures are essential for the early detection and treatment of animals. As a conclusion, it is evident that, although there is documentation regarding the disease, the truth is that greater attention is required by researchers, farmers and the State in Colombia